2002
DOI: 10.1161/hc0202.102248
|View full text |Cite
|
Sign up to set email alerts
|

Activated Monocytes Induce Smooth Muscle Cell Death

Abstract: Background — Plaque disruption is the inciting event for coronary thrombosis and acute coronary syndromes. Multiple factors influence plaque rupture, including the loss of vascular smooth muscle cells (VSMCs). We hypothesized that monocytes/macrophages (MMs) activated by macrophage colony-stimulating factor (M-CSF) are responsible for VSMC death. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…In this study, activated monocyte-induced HRPE cell apoptosis was reduced by anti-CD18 (␤2 integrin) antibody. Our result is in agreement with previous reports that have shown the involvement of ␤2 integrins in smooth muscle cell apoptosis induced by monocytes activated with macrophage colony-stimulating factor; in HLA-DR-mediated monocyte apoptosis; in Fasmediated, monocyte-dependent, T lymphocyte apoptosis; in superantigen-induced death of specific CD4 ϩ T-lymphocytes; and in TNF-␣-induced neutrophil apoptosis (Damle et al, 1993b;Seshiah et al, 2002;Thibeault et al, 1999;Walzog et al, 1997;Wu et al, 1996). Previous studies have shown that the CD18-ICAM-1 adhesion pathway is important in the recognition of target cells and in monocyte-induced cytotoxicity of vascular endothelial cells and tumor cells (Bernasconi et al, 1991;Jonjic et al, 1992).…”
Section: Yoshida Et Alsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, activated monocyte-induced HRPE cell apoptosis was reduced by anti-CD18 (␤2 integrin) antibody. Our result is in agreement with previous reports that have shown the involvement of ␤2 integrins in smooth muscle cell apoptosis induced by monocytes activated with macrophage colony-stimulating factor; in HLA-DR-mediated monocyte apoptosis; in Fasmediated, monocyte-dependent, T lymphocyte apoptosis; in superantigen-induced death of specific CD4 ϩ T-lymphocytes; and in TNF-␣-induced neutrophil apoptosis (Damle et al, 1993b;Seshiah et al, 2002;Thibeault et al, 1999;Walzog et al, 1997;Wu et al, 1996). Previous studies have shown that the CD18-ICAM-1 adhesion pathway is important in the recognition of target cells and in monocyte-induced cytotoxicity of vascular endothelial cells and tumor cells (Bernasconi et al, 1991;Jonjic et al, 1992).…”
Section: Yoshida Et Alsupporting
confidence: 94%
“…Direct cell-to-cell contact has also been shown to influence cellular response, function, and survival in many kinds of cell types (Meszaros et al, 2000;Seshiah et al, 2002;Yoshida et al, 2001a). HRPE cells are frequently associated with monocytes in PVR, ARMD, and uveitis (Baudouin et al, 1992;Chan et al, 1985;Harper et al, 1992;Jerdan et al, 1989;Kampik et al, 1981;Vinores et al, 1990).…”
mentioning
confidence: 99%
“…17 The reason is not quite clear, but it seems that SMCs play an important role in preserving the integrity of the extracellular matrix in the cap. 18,19 Furthermore, mechanical overstretching has proven to induce apoptosis in isolated vascular smooth muscle cells. 20 In our study, this phenomenon may be exemplified by the fact that high strain is correlated with a low amount of SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FasL localizes to apoptotic SMC in advanced lesions and induces apoptosis of SMC in vitro (21,22). In addition, the cellular effectors of immune-mediated apoptosis in atherosclerotic plaques are likely T cells and macrophages, as these leukocytes have been implicated in SMC apoptosis and in the development of acute coronary syndromes (8,(23)(24)(25)(26)(27). Our association of granzyme B immunoreactivity with advanced atherosclerotic disease, and localization of granzyme B to apoptotic cells, suggests that this cytotoxic immune factor may further contribute to acute coronary syndromes through a similar mechanism as FasL.…”
Section: Discussionmentioning
confidence: 99%